Perceptions governing the adoption of biomimicry in the UAE construction industry - Abdulmaksoud, Sara; Joseph, Tania M.; Al Suwaidi, Khalid; Alghoush, Mohamad; Atabay, Serter; Beheiry, Salwa (Frontiers in Built Environment, 2025)
Despite the significant potential of biomimicry to advance sustainability in the UAE’s rapidly urbanizing construction sector, its widespread adoption is hindered by critical contextual challenges and implementation barriers. Therefore, this study investigates the critical factors shaping stakeholders’ perceptions of biomimicry adoption as a sustainable construction strategy in the UAE. Given the region’s rapid urban development and environmental challenges, understanding these perceptions is essential for identifying enablers and inhibitors of adoption. A hypothetical model comprising six latent dimensions: knowledge, social, environmental, resource, regulatory, and risk, was empirically tested using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) based on data collected through a structured survey targeting UAE construction professionals. The results demonstrate that knowledge, regulatory, and risk factors significantly influence stakeholder perceptions and intentions to adopt biomimicry. To complement these insights, the Relative Importance Index (RII) was applied to rank specific indicators within each dimension, offering granular perspectives on stakeholder priorities. The findings emphasize the need for targeted educational programs, policy reforms, and risk mitigation strategies to facilitate biomimicry integration and support the UAE’s broader sustainability agenda.